The Existence of Social Media on Behavior State Junior High School Students - Ismail Ismail (Didaktika: Jurnal Kependidikan, 2023)
This study discusses how the existence of social media affects the behaviour of students at SMP Negeri 1 in the North Belopa District. This type of research uses a qualitative research type with a phenomenological approach. The phenomenon observed is related to social media and its impact on students' behaviour at State Middle Schools in North Belopa District. The research subjects were junior high school students in North Belopa, focusing on social media such as Facebook or Twitter. Data collection methods, such as interviews, participatory observation, and document analysis, are commonly used in qualitative research. Data analysis techniques use the theory of Miles and Huberman: data reduction, data display, and data verification by checking the validity of the data using Credibility, Transferability, Dependability, and Confirmability. Students at State Middle School in North Belopa District use social media as a platform to show their existence to the outside world. Everyone competes to display and create branding about himself to the outside world. Through various photos, videos, and statements on social media, someone wants to express to others that this is who they are. Not infrequently, even a person can act excessively to show his existence to others. Someone wants to reveal to others that this is who he is. Not infrequently, even a person can act excessively to show his existence to others. Someone wants to reveal to others that this is who he is. Not infrequently, even a person can act excessively to show his existence to others.